2023
DOI: 10.1085/jgp.202213247
|View full text |Cite
|
Sign up to set email alerts
|

Screening for bilayer-active and likely cytotoxic molecules reveals bilayer-mediated regulation of cell function

Abstract: A perennial problem encountered when using small molecules (drugs) to manipulate cell or protein function is to assess whether observed changes in function result from specific interactions with a desired target or from less specific off-target mechanisms. This is important in laboratory research as well as in drug development, where the goal is to identify molecules that are unlikely to be successful therapeutics early in the process, thereby avoiding costly mistakes. We pursued this challenge from the perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 139 publications
0
9
0
Order By: Relevance
“…In fact, a recent study showed that amphiphilic drugs, which change membrane properties, cause indiscriminate changes in membrane protein function and, in turn, even cytotoxicity. 57 The present work has some limitations. First, while our findings strongly suggest a membrane-mediated mechanism for the modulation of ASICs by TA, we cannot prove actual interaction with the membrane nor can we exclude direct interaction with ASICs.…”
Section: ■ Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, a recent study showed that amphiphilic drugs, which change membrane properties, cause indiscriminate changes in membrane protein function and, in turn, even cytotoxicity. 57 The present work has some limitations. First, while our findings strongly suggest a membrane-mediated mechanism for the modulation of ASICs by TA, we cannot prove actual interaction with the membrane nor can we exclude direct interaction with ASICs.…”
Section: ■ Discussionmentioning
confidence: 85%
“…Our data showing that TA, PG, and GT lack selectivity for membrane proteins, particularly ion channels, suggest that they have limited potential for clinical applications. In fact, a recent study showed that amphiphilic drugs, which change membrane properties, cause indiscriminate changes in membrane protein function and, in turn, even cytotoxicity …”
Section: Discussionmentioning
confidence: 99%
“…Drug-induced changes in the ANTS quench rate thus reflect the bilayer-modifying potency of a compound, 49, 50 and changes in rate / rate control > 1.5 are associated with increased risk that the compound may be cytotoxic. 21 In initial testing, IVM significantly increased the ANTS quench rate at 10 µM ( Figure 5A ). In concentration-response testing, IVM increased the ANTS quench rate in a concentration-dependent manner, with 1 μM IVM increasing the rate relative to DMSO control 12-fold indicating that IVM is a potent bilayer modifier at this concentration ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 93%
“…This is consistent with previous observations showing a correlation between membrane bilayer-modifying properties and cytotoxicity. 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation